Poverty reduction and growth : virtuous and vicious circles - Perry, Guillermo (World Bank Latin American and Caribbean studies., 2006)
"Poverty Reduction and Growth: Virtuous and Vicious Circles is about the existence of vicious circles in Latin America and the Caribbean and about the ways and means to convert them into virtuous circles in which poverty reduction and high growth reinforce each other. Through its analysis of fresh data and the attention it pays to issues such as the persistent inequality in the region, the role played by various microdeterminants of income, and the potential existence of human capital underinvestment traps, Poverty Reduction and Growth: Virtuous and Vicious Circles should be a valuable contribution to the current regional debate on poverty and growth."--Jacket